Comparative Study of Fatty Acid Composition in Crude Vegetable Oils from Species Cultivated in Mato Grosso do Sul, Brazil - Érico Vinícius Rocha Sanches; Geovanna Vilalva Freire; Simone Reis Santos; Gláucia Braz Alcantra; João Batista Gomes de Souza (Orbital: The Electronic Journal of Chemistry, 2023)
Soybean is the main oilseed cultivated in the Middle-west region of Brazil, once geoclimatic conditions favor its cultivation and underexplored species such as crambe, oilseed radish, and niger too. These species can be alternatives to eliminate the conflict between food and energy production, so the study aimed to evaluate and compare the fatty acids content of soybean, crambe, oilseed radish and niger oils by gas chromatography with flame ionization detector using two quantification methods, followed by multivariate statistical analysis to determine the similarity between the selected species and to provide safe information for the best selection and application of these oilseeds. The oil content in crambe, oilseed radish and niger seeds were 44.7% (m/m), 42.45% (m/m) and 28.19% (m/m), respectively. The major fatty acid in niger and soybean oils was linoleic acid (66.9% and 52.07% m/m, respectively), in crambe and oilseed radish was erucic acid (65.29% and 33.54% m/m, respectively). In addition, for saturated fatty acids, the presence is minor (<17%), except for niger seeds with 19.5% (m/m). Niger oil has greater similarity with soybean oil, whereas crambe and oilseed radish oils are more similar to each other. In this way, it was possible to discriminate the different fatty acids present in the oil samples by the proposed method contributing to the objective of the study and enabling better decision-making in the context like biofuels production.